Nicolas Arnoldus (1618–1680)—the Migrating Man in Pierre Bayle’s Dictionnaire historique et critique - Jakuboszczak, Agnieszka; Forycki, Maciej (Sensus Historiae, 2024)
This article analyses the biography of Mikołaj Arnoldus (1618–1680) as it appears in Pierre Bayle’s Dictionnaire historique et critique (1647–1706), published in 1697. The work examined is one of the important texts of the Enlightenment and is marked by criticism. The focus is on its mobility: the directions it took and the circumstances that accompanied them. Attention is paid to the religious context accompanying this migration and to Mikołaj Arnoldus’s integration into the communities in which he settled: the university establishment and Calvinist society.